Kajian Hasil Uji Mutu dan Rencana Biaya Penggunaan Sambungan Mechanical Coupler - Gita Puspa Artiani; Achmad Pahrul Rodji; Ferry Anggriawan (Fakultas Teknik Universitas Krisnadwipayana, 2023)
The construction of the Jakarta Kemayoran Tower was carried out using a mechanical coupler connection in the building column construction, because overlapping or conventional connections are not the right way to connect reinforcement. The main reinforcement in the column uses threaded iron with a diameter of 25. The mechanical coupler connection method used in this study is a coupler grip, with the planned tensile strength of the reinforcing steel being 525 N/mm². The column structure that is sampled is the main column with the size of the main steel reinforcement ≥ 32 mm. This study focuses on the analysis of quality tests and cost plans. The analytical approach used is descriptive analysis by looking for a comparison of the two variables. Testing the tensile strength of concrete reinforcement using a mechanical coupler connection showed successive results of 621.04 MPa, 624.86 MPa, 625.41 MPa, these results exceeded the minimum limit specified in SNI-2052-2017, namely 525 MPa. Meanwhile, the calculation of connection costs using the mechanical coupler method requires a total cost of Rp. 139,824,000, - while the cost of using a conventional connection is Rp. 191.161.127,-. From the calculation results, it is obtained that the difference is 37% cheaper than conventional reinforcement connections.This research can be used as a reference in alternative selection of reinforcement joints.